Characterization and technological potential of underutilized ancestral andean crop flours from ecuador - Salazar, Diego; Arancibia, Mirari; Ocaña, Iván; Rodríguez-Maecker, Roman; Bedón, Mauricio; López-Caballero, María Elvira; Montero, María Pilar (MDPI, 2022)
Ancestral Andean crop flours (ACF) from Ecuador such as camote (Ipomea Batatas), oca (Oxalis tuberosa), achira (Canna indica), mashua (Tropaeolum tuberosum), white arracacha (Arracacia xanthorrhiza), taro (Colocasia esculenta) and tarwi (Lupinus mutabilis sweet) were characterized in terms of physico-chemical and techno-functional properties in order to identify their potential as new alternative ingredients in food products. Flour from camote, oca, achira and arracacha showed a low protein content (<5%), mashua and taro had ~9% and tarwi flour registered higher values than 52%. Carbohydrate content ranged from 56–77%, with the exception of tarwi, just reaching 6.9%. Starch content was relatively low in ACF but in taro and tarwi, starch practically constituted almost all the carbohydrates. The highest amylose content in starch, in decreasing order, was found in mashua, oca, tarwi and achira flours, the rest being ≤15%. Fiber content exceeded 10% in most crops, except for oca flour with 5.33%. Fat content was generally lower than 1%, except in tarwi with ~17%. All flours showed a gel-like behavior G′ > G′′, this being very similar in camote, achira and tarwi flours. The exception was taro with G′ < G′′. Mashua flour registered the highest value for phenol content (60.8 µg gallic acid equivalents/g of sample); the content of phenols was not exclusively responsible for the antioxidant activity, since flours with the highest activity were arracacha and tarwi, which presented the lowest phenol content among all flours. Principal component analyses (PCA) showed a high correlation between moisture, fiber, solubility and water absorption capacity, with viscoelastic behavior and total phenolic content; while starch content was correlated with melting temperature, poorly and inversely related to protein and fat. For PC1, achira, camote and taro flours were very similar, and different from oca and mashua flours. Tarwi showed its own characteristics according to PC1 and 2. Because of their properties, Andean crop flours could have a great potential for use in food technology.
Keywords: andean crop flours; antioxidant; functional proper-ties; morphology; physico-chemical characteristic; Scopus; JCR